Reaction of oxiranes with cyclodextrins under high-energy ball-milling conditions - Jicsinszky, László; Calsolaro, Federica; Martina, Katia; Bucciol, Fabio; Manzoli, Maela; Cravotto, Giancarlo (Beilstein Journal of Organic Chemistry, 2019)
This work presents a proof of concept for a green cyclodextrin derivatisation method that uses low-boiling epoxide reagents in a high-energy ball mill (HEBM). The simplified preparation and purification of low substitution-degree common (2-hydroxy)propylated β- and γ-cyclodextrins (β/γ-CDs) has been realised. The intelligent use of propylene oxide has also facilitated the more effective synthesis of highly substituted γ-CD. Epichlorohydrin-crosslinked CD-polymers (CDPs) have also been effectively prepared in the ball mill. The unoptimised preparations of soluble and insoluble CDPs displayed very small particle size distributions, while the prepared polymers currently have different complexation properties to those of their classically prepared analogues.
Keywords: crosslinked cyclodextrin polymers; (2-hydroxy)propylcyclodextrin; mechanochemistry; nucleophile reaction; planetary ball mill; solventless synthesis

Comprehensive Supramolecular Chemistry - Szejtli, J.; Osa, T. (Cyclodextrins, 1996)

Cyclodextrins in Pharmaceutics, Cosmetics, and Biomedicine - Trotta, F. (Cyclodextrin Nanosponges and Their Applications, 2011)

Reactivity and Analysis - Řezanka, M. (Synthesis of Cyclodextrin Derivatives. Cyclodextrin Fundamentals, 2018)

(untitled) - Gelb, R. I.; Schwartz, L. M.; Laufer, D. A. (Bioorg. Chem., 1982)

(untitled) - Gelb, R. I.; Schwartz, L. M.; Bradshaw, J. J.; Laufer, D. A. (Bioorg. Chem., 1980)

Hungarian Patent - Szabo, T.; Szejtli, J.; Szente, L.; Horvath, G.; Peterdi, V.; Szeman, J.; Toth, A.; Komar, P. (Process for producing 2-hydroxy-propyl-alpha-, beta- and gamma-cyclodextrin, 1991)

Hungarian Patent - Jicsinszky, L.; Szejtli, J.; Szente, L.; Ujhazy, A.; Weiszfeiler, V. (Process for Purifying Alkylated and Hydroxyalkylated Cyclodextrins and for Reducing Their Unsubstituted Cyclodextrin Content, 1991)

Minutes of the 6th International Symposium on Cyclodextrins - Vikmon, M.; Gerloczy, A.; Fenyvesi, E.; Jicsinszky, L. (Comparative Characterization of Complex-forming Ability of HP-beta-CDs with Phenolphthalein, Chicago, Il, 21.4.1992-24.4.1992, 1992)

(untitled) - Pitha, J.; Trinadha Rao, C.; Lindberg, B.; Seffers, P. (Carbohydr. Res., 1990)

(untitled) - Müller, B. W.; Brauns, U. (J. Pharm. Sci., 1986)

(untitled) - Buvári-Barcza, Á.; Bodnár-Gyarmathy, D.; Barcza, L. (J. Inclusion Phenom. Mol. Recognit. Chem., 1994)

(untitled) - Jicsinszky, L.; Caporaso, M.; Calcio Gaudino, E.; Giovannoli, C.; Cravotto, G. (Molecules, 2017)

Proceedings of the Fourth International Symposium on Cyclodextrins - Fenyvesi, E.; Decsei, L.; Ujhazy, A.; Zsadon, B.; Szejtli, J. (Complexes of Insoluble Cyclodextrin Polymers, Munich, West Germany, 20.4.1988-22.4.1988, 1988)

(untitled) - Malanga, M.; Bálint, M.; Puskás, I.; Tuza, K.; Sohajda, T.; Jicsinszky, L.; Szente, L.; Fenyvesi, É. (Beilstein J. Org. Chem., 2014)

(untitled) - Solms, J.; Egli, R. H. (Helv. Chim. Acta, 1965)

Swiss Patent - Solms, J. (Process for the Preparation of Inclusion Complexes of High Molecular Weight, 1964)

(untitled) - Yuan, D.-Q.; Tahara, T.; Chen, W.-H.; Okabe, Y.; Yang, C.; Yagi, Y.; Nogami, Y.; Fukudome, M.; Fujita, K. (J. Org. Chem., 2003)

(untitled) - Hishiya, T.; Shibata, M.; Kakazu, M.; Asanuma, H.; Komiyama, M. (Macromolecules, 1999)

(untitled) - Mallard, I.; Baudelet, D.; Castiglione, F.; Ferro, M.; Panzeri, W.; Ragg, E.; Mele, A. (Beilstein J. Org. Chem., 2015)

U.S. Patent - Pitha, J. (Selective Alkylations of Cyclodextrins Leading to Derivatives Which Have a Rigidly Extended Cavity, 1997)

(untitled) - Zsadon, B.; Décsei, L.; Szilasi, M.; Tüdős, F.; Szejtli, J. (J. Chromatogr., 1983)

(untitled) - Szejtli, J.; Fenyvesi, É.; Zsadon, B. (Starch/Staerke, 1978)

(untitled) - Zsadon, B.; Szilasi, M.; Décsei, L.; Ujházy, A.; Szejtli, J. (J. Chromatogr., 1986)

(untitled) - Zsadon, B.; Ács, M.; Fogassy, E.; Faigl, F.; Novak, C.; Pokol, G.; Ujházy, A. (React. Polym., Ion Exch., Sorbents, 1987)

(untitled) - Cravotto, G.; Caporaso, M.; Jicsinszky, L.; Martina, K. (Beilstein J. Org. Chem., 2016)

(untitled) - Stolle, A.; Szuppa, T.; Leonhardt, S. E. S.; Ondruschka, B. (Chem. Soc. Rev., 2011)

Comprehensive Organic Synthesis - Hernández, J. G.; Avila-Ortiz, C. G.; Juaristi, E. (Useful Chemical Activation Alternatives in Solvent-Free Organic Reactions, 2014)

(untitled) - Do, J.-L.; Friščić, T. (ACS Cent. Sci., 2017)

(untitled) - Jicsinszky, L.; Caporaso, M.; Martina, K.; Calcio Gaudino, E.; Cravotto, G. (Beilstein J. Org. Chem., 2016)

Japanese Patent - Tokuda, K.; Morii, S.; Kazuhiko, Y. (Novel Cyclodextrin Derivative and Production Thereof, 1986)

U.S. Patent - Gramera, R. E.; Caimi, R. J. (Cyclodextrin Polyethers and their Production, 1996)

Chinese Patent - Zheng, L.; Liang, M.; Wang, S.; Liu, X.; Qi, Y.; He, Y.; He, L. (Preparation Method of Hydroxypropyl-beta-cyclodextrin, 2012)

Cyclodextrins - Jicsinszky, L.; Fenyvesi, E.; Hashimoto, H.; Ueno, A. (Cyclodextrin derivatives, 1996)

Minutes of 6th Int. Symp. Cyclodextrins - Pitha, J. ((Hydroxypropyl)cyclodextrins, mixtures are beautiful if properly characterized, Chicago, Il, 21.4.1992-24.4.1992, 1992)

(untitled) - Trinadha Rao, C.; Pitha, J.; Lindberg, B.; Lindberg, J. (Carbohydr. Res., 1992)

(untitled) - Mischnick, P. (Carbohydr. Res., 1989)

EMA/CHMP/704195/2013

Cyclodextrins: Chemistry and Physics - Krause, R.; Mamba, B. B.; Bambo, M.; Malefetse, T. J. (Cyclodextrin polymers: Synthesis and Application in Water Treatment, 2011)

(untitled) - Jicsinszky, L.; Caporaso, M.; Tuza, K.; Martina, K.; Calcio Gaudino, E.; Cravotto, G. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Crini, G.; Bertini, S.; Torri, G.; Naggi, A.; Sforzini, D.; Vecchi, C.; Janus, L.; Lekchiri, Y.; Morcellet, M. (J. Appl. Polym. Sci., 1998)

(untitled) - Crini, G.; Cosentino, C.; Bertini, S.; Naggi, A.; Torri, G.; Vecchi, C.; Janus, L.; Morcellet, M. (Carbohydr. Res., 1998)

(untitled) - Komiyama, M.; Hirai, H. (Polym. J., 1987)

Japanese Patent - Harada, K.; Morimoto, S. (Production of Bead-foam Insoluble Cyclodextrin Polymer, 1983)

German Patent - Szejtli, J.; Fenyvesi, E.; Sarkoezi, P.; Felmeray, I.; Zsoldos, A. (Pharmaceuticals Containing Cyclodextrin-iodine Inclusion Compounds for Controlled Release of Iodine, 1988)

(untitled) - Másson, M.; Pitha, J.; Loftsson, T. (J. Inclusion Phenom. Macrocyclic Chem., 1999)

U.S. Patent - Pitha, J. (Preparation of Dioxane-substituted Cyclodextrin Macromolecules and Inclusion Complexes with Cholesterol and Hydrocortisone, 1999)

U.S. Patent - Pitha, J. (Alkylations of Cyclodextrins with Epichlorohydrin Leading to Derivatives Which Have a Rigidly Extended Cavity, 1999)